China and the world's first freedom of information act - Rydholm, Lena (Javnost (Ljubljana), 2013)
In 1766, the world's first freedom of information act: His Majesty's Gracious Ordinance Relating to Freedom of Writing and of the Press was passed in the Swedish Diet, largely through the work of Anders Chydenius. Few people today realise that this had something to do with China. The image of China as a distant utopia, a prosperous and politically stable country, had been created through accounts such as Jean Baptiste Du Halde's four volume Description géographique, historique, chronologique, politique, et physique de l'empire dela Chine et de la Tartarie chinoise. In Sweden, politicians Anders Nordencrantz and Anders Chydenius, basing their arguments on Du Halde's descriptions, claimed that the freedom of writing, of the press and of information had been in existence in China since ancient times, and had largely contributed to the wealth and stability of China. In this paper I examine the political pamphlets written by these two Swedish politicians to show how they used China as an example to strengthen the arguments for a Freedom of the Press Act in Sweden.
Keywords: Kitajska; Švedska; svoboda tiska; svoboda informiranja; človekove pravice; human rights; pravna ureditev